Depression among female patients in medical wards - Al-Ani, Ali Sabri; Al – Azzawi, Reyad (2011)
Background: Depression is a common psychiatric disorder and numerous studies have found associations between depression and physical illnesses among general hospital in – patients. Objectives: This study aims to identify the rate of depression and its severity among female patients in medical wards and to find out the relation between depression and clinical type of medical diagnosis classified by systems of the body. Methods: 50 adult female patients were taken from the medical in- patients of Al-Yarmook Teaching Hospital and Al-Numan General Hospital in Baghdad / Iraq over a period f a three months. The patients were assessed for the presence of depression by a semi – structured psychiatric interview schedule based on ICD-10 criteria. The severity of depression was rated by Beck depression Inventory. The patients group was matched for age with 50 normal control females to achieve comparability. Results: The results showed that the rate of depression in adult female patients in medical wards was 44% which was 1.7 times higher than that among their matched normal control subjects. (P-value <0.05). The majority of the depressed patients group (45.45%) had moderate depression, which was statistically significant. (P-value <0.05). 36.36% of the depressed patients were in the age group (41-50) years, and the majority of the depressed patients were married, housewives, achieved primary school education and having low income. There were no significant differences regarding medical diagnosis classified by system. Conclusion: In conclusion, depression is common among female patients in medical wards.